Current Activities in Smokes-Free Zone Policy: a Tobacco Control Care Reviews in Indonesia - Meita Veruswati; Al Asyary; Mardiati Nadjib; Anhari Achadi (Family Medicine & Primary Care Review, 2018)
Although the Republic of Indonesia’s government has not yet ratified the World Health Organization’s Framework Convention on Tobacco Control (WHO FCTC), this nation has started to implement tobacco control care by establishing smoke-free zones (SFZs). We describe and explore the current SFZ activities in Indonesia as well as briefly reviewing tobacco control care in developing countries by examining several documents on the current activities and programs related to SFZ implementation policy in Indonesia. We find that there is evidence supporting current primary activities on tobacco control care, including smoking prevalence, regulation, objectives, and the target of SFZ implementation in Indonesia. The policy introduced seven SFZs, including healthcare facilities, educational settings, children’s playgrounds or gathering places for children, places of worship, public transportation, workplaces, and public places. Several developed countries such as the United States have implemented a well-packaged and well-delivered SFZ policy with effective socialization. However, a mutual perception issue is emerging in implementing this policy well from central to local government policies. This essential matter requires study, as there is limited evidence on the barriers and outcomes of its comprehensive implementation.